Case report: biallelic DNMT3A mutations in acute myeloid leukemia - Cumbo, Cosimo; Orsini, Paola; Anelli, Luisa; Zagaria, Antonella; Iannò, Maria Federica; De Cecco, Loris; Minervini, Crescenzio Francesco; Coccaro, Nicoletta; Tota, Giuseppina; Parciante, Elisa; Conserva, Maria Rosa; Redavid, Immacolata; et al. (Frontiers in Oncology, 2023)
DNMT3A gene mutations, detected in 20-25% of de novo acute myeloid leukemia (AML) patients, are typically heterozygous. Biallelic variants are uncommon, affecting 3% of cases and identifying a worse prognosis. Indeed, two concomitant DNMT3A mutations were recently associated with shorter event-free survival and overall survival in AML. We present an AML case bearing an unusual DNMT3A molecular status, strongly affecting its function and strangely impacting the global genomic methylation profile. A 56-year-old Caucasian male with a diagnosis of AML not otherwise specified (NOS) presented a complex DNMT3A molecular profile consisting of four different somatic variants mapping on different alleles (in trans). 3D modelling analysis predicted the effect of the DNMT3A mutational status, showing that all the investigated mutations decreased or abolished DNMT3A activity. Although unexpected, DNMT3A's severe loss of function resulted in a global genomic hypermethylation in genes generally involved in cell differentiation. The mechanisms through which DNMT3A contributes to AML remain elusive. We present a unique AML case bearing multiple biallelic DNMT3A variants abolishing its activity and resulting in an unexpected global hypermethylation. The unusual DNMT3A behavior described requires a reflection on its role in AML development and persistence, highlighting the heterogeneity of its deregulation.